COMPARISON OF SOCIAL SCIENCE LEARNING RESULTS USING COOPERATIVE LEARNING MODELS OF THINK PAIR SHARE AND NUMBERED HEADS TOGETHER TYPE - Haliadi; Satibi, Otib; Muji Utami, Nidya Chandra (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to find out the significant differences in student learning outcomes by using the Think Pair Share and Numbered Heads Together cooperative learning models. The research method used is quantitative with the type of experimental research. The location of this study was carried out at State Elementary School 1 Patuno, Wangi-wangi District, Wakatobi Regency. After the test, the average learning outcome of the first experimental class was 80, while in the second experimental class of 71.75, it was seen that the average score in the first experimental class was higher than the average score of the second experimental class. Based on the results of the t-test, it can be seen that there is a significant difference in the learning outcomes of students in Social Sciences taught using the Think Pair Share and Numbered Heads Together type cooperative learning model in grade IV of State Elementary School 1 Patuno, where Ha is accepted with a ttable >  tcount of 2.33008 > 1.72472 at the level  of α = 0.05 with a difference of 11.49%. The Think Pair Share model is more effective for Social Science learning than Numbered Heads Together, because it is able to increase student activity and interaction in the learning process. TPS is able to encourage more active student participation, increase interaction between students, and provide greater opportunities for students to share and develop understanding through discussion. Keywords: Learning Outcomes; Numbered Heads Together; Think Pair Share